2014
DOI: 10.1038/srep04396
|View full text |Cite
|
Sign up to set email alerts
|

Evidence For Rapid Spatiotemporal Changes in Genetic Structure of an Alien Whitefly During Initial Invasion

Abstract: The sweetpotato whitefly Bemisia tabaci Q species is a recent invader and important pest of agricultural crops in China. This research tested the hypothesis that the Q populations that establish in agricultural fields in northern China each year are derived from multiple secondary introductions and/or local populations that overwinter in greenhouses (the pest cannot survive winters in the field in northern China). Here, we report the evidence that the Q populations in agricultural fields mainly derive from mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…The genetic diversity of species is closely associated with their ecological adaptations, which have been explored in many species especially in invasive alien species192324. In this study, unique mtCOI haplotypes have been identified in many populations from the GMS, which indicates that the adaptation of these haplotypes are a response to the local environment including the unique climate, host plants, and agricultural activities experienced by the population from that particular region.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The genetic diversity of species is closely associated with their ecological adaptations, which have been explored in many species especially in invasive alien species192324. In this study, unique mtCOI haplotypes have been identified in many populations from the GMS, which indicates that the adaptation of these haplotypes are a response to the local environment including the unique climate, host plants, and agricultural activities experienced by the population from that particular region.…”
Section: Discussionmentioning
confidence: 74%
“…Approaches involving population genetics such as the use of mitochondrial and nuclear microsatellite markers can provide essential tools for overcoming these problems151617181920. Previous study has demonstrated the genetic differentiation in S. furcifera from five disjunct localities in Korea, the Philippines, China (only two populations), Malaysia, and Vietnam using mitochondrial sequences.…”
mentioning
confidence: 99%
“…had in 2009, but we failed to detect the Q biotype using the specific mtCOI primers used in the present study (see section 2.2) or mtCOI sequencing as in our previous research31, implying that the Q biotype previously invaded Fujian, but failed to colonize it before 2012. Multiple secondary introductions, however, may be an important prerequisite for the establishment of the Q population in the fields37.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, high temperatures ≥35 °C, which appear in the open fields and often exist in protected areas, may have contributed to the results in this paper, specifically the colonization of the Q biotype and its proportional increase in whitefly population. Chu et al 37. demonstrated that wide use of the protected agriculture in northern China promoted the colonization of the Q biotype in agricultural fields.…”
Section: Discussionmentioning
confidence: 99%
“…Following its introduction to new areas, B. tabaci Med is replacing the previously common B. tabaci MEAM1 (e.g. Chu et al 2010, Pan et al 2011, and multiple introductions from several sources to a particular area can contribute to increased genetic diversity potentially leading to improved adaptation to new environments (Chu et al 2014 …”
Section: Introductionmentioning
confidence: 99%